Development of Integrated STEM Teaching Materials to Enhance Learning Outcomes in Primary School Science Education - Maya Purnamaningtyas; Suryanti; Farida Istianah (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
This study aims to develop integrated STEM teaching materials to improve science learning outcomes for fourth-grade students. Preliminary research revealed several shortcomings in current teaching materials, including insufficient glossary entries, underutilization of digital resources, and gaps in curriculum alignment due to recent updates. Additionally, the results of the Cambridge Progression Test 2024 indicated that students at Little Sun School scored below the national average in science, with 72% of students performing below the benchmark. To address these issues, this research proposes the development of STEM-integrated teaching materials that include comprehensive glossaries, interactive digital tools, and project-based learning activities. The goal is to create materials that enhance student engagement, foster critical thinking, and support independent learning. By integrating STEM principles, the new materials aim to bridge the gaps in students’ understanding, improve conceptual clarity, and ultimately elevate science achievement. The findings suggest that well-designed STEM materials have the potential to significantly enhance both the quality of teaching and students' learning outcomes